2001
DOI: 10.1046/j.1526-0968.2001.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Human Preconditioned Phagocytes for Extracorporeal Immune Support: Introduction of a Concept

Abstract: Neutrophils are critical effector cells in humoral and innate immunity and play a vital role in phagocytosis and bacterial killing. If they and/or their specific functions are lacking, then immunoparalysis may occur, and severe diseases like systemic inflammatory response syndrome (SIRS) or sepsis can take a fatal course. In this paper, we discuss the possibility of using preconditioned cells in an extracorporeal biohybrid immune support system. A human promyelocytic cell line was stimulated for different time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…The efficient removal of live bacteria by granulocytes was both proven in vitro and in the pig-bacteremia model [14,15]. There is already good evidence for removal of bacterial endotoxins as well as interaction on the mediator and cytokine level during this clinical study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The efficient removal of live bacteria by granulocytes was both proven in vitro and in the pig-bacteremia model [14,15]. There is already good evidence for removal of bacterial endotoxins as well as interaction on the mediator and cytokine level during this clinical study.…”
Section: Discussionmentioning
confidence: 86%
“…In in vitro studies [14] and in a large animal model for Gram-positive sepsis [15], we were able to show the proof of principle and promising survival data. Therefore, the bioreactor is now being studied in patients with septic shock in order to show tolerability and feasibility of this kind of complex therapy.…”
Section: Introductionmentioning
confidence: 95%
“…Cell differentiation was induced by 1ϫ10E-5 M all-trans retinoic acid (HoffmannLaRoche, Grenzach-Wyhlen, Germany) for 5 days. After differentiation, the cells showed a phenotype of functional granulocytes with increased production of oxygen radicals, active intracellular killing, and increased phagocytosis with a high reduction rate of Escherichia coli, Staphylococcus aureus, and Candida albicans (28).…”
Section: Cell Cultures and Preparation Of Bacteriamentioning
confidence: 99%
“…The rationale for such an approach is that on one hand the plasma-modifying capacity of human phagocytes can be used (e.g., to remove antigenic material from the circulation) while on the other hand control over these cells can be maintained (e.g., retention of the cells, their release and breakdown-products; preventing local tissue effects), thereby avoiding potential side effects triggered by GTx. Previous studies revealed that relevant amounts of live and dead bacteria can be removed from human plasma using a phagocytosis cell device (28). Here, we describe the use of such a system in a well-described pig model of multiresistant Gram-positive sepsis (29,30) resembling an onset of sepsis in cases where empirical use of antibiotics fails.…”
mentioning
confidence: 99%
“…Recently, we demonstrated that a phagocytosis cell device is able to remove living and dead bacteria from plasma at a rate of >70% (in vitro studies) (17). The extracorporeal treatment with the cell device can improve the survival in a pig model of sepsis (18).…”
mentioning
confidence: 99%